Steering acidic oxygen reduction selectivity of single-atom catalysts through the second sphere effect - Haiyuan Zou; Siyan Shu; Wenqiang Yang; You-chiuan Chu; Minglun Cheng; Hongliang Dong; Hong Liu; Fan Li; Junhui Hu; Zhenbin Wang; Wei Liu; Hao Ming Chen; et al. (Nature Communications)
Abstract Natural enzymes feature distinctive second spheres near their active sites, leading to exquisite catalytic reactivity. However, incumbent synthetic strategies offer limited versatility in functionalizing the second spheres of heterogeneous catalysts. Here, we prepare an enzyme-mimetic single Co–N4 atom catalyst with an elaborately configured pendant amine group in the second sphere via 1,3-dipolar cycloaddition, which switches the oxygen reduction reaction selectivity from the 4e− to the 2e− pathway under acidic conditions. Proton inventory studies and theoretical calculations reveal that the introduced pendant amine acts as a proton relay and promotes the protonation of *O2 to *OOH on the Co–N4 active site, facilitating H2O2 production. The second sphere-tailored Co–N4 sites reach optima H2O2 selectivity of 97% ± 1.13%, showing a 3.46-fold enhancement to bare Co–N4 catalyst (28% ± 1.75%). This work provides an appealed approach for enzyme-like catalyst design, bridging the gap between enzymatic and heterogeneous catalysis.